ANTESEDEN DAN KONSEKUENSI EFEKTIVITAS KINERJA MANAJERIAL TERHADAP KUALITAS KREDIT DI BPR NUSAMBA WILAYAH BALI - Ni Made Wisni Arie Pramuki; Putu Cita Ayu; Ni Wayan Ary Astini (Faculty of Economics and Business, Universitas Warmadewa, 2023)
This study aims to examine the internal control system on managerial performance in order to improve credit quality. This research was conducted at BPR Nusamba Bali Region by distributing research questionnaires. The samples involved in this study were 72 respondents. The data analysis method using SEM PLS. The results of the study indicate that the internal control system in this study is an antecedent in an effort to improve credit quality at BPR Nusamba, Bali Region